Power, Solidarity and the Construction of Requests in Service Encounters - Bastos, Liliana Cabral (The ESPecialist, 2012)
This paper presents the analysis of service encounters which took place at the counter of the social/health office of a Brazilian public company. The data, collected in an ethnographically oriented research project, was analysed within a social-interactional approach to discourse. The focus of the analysis is on the different strategies clients use to ask for information and to demand for administrative services. It was observed that, among other things, these strategies vary according to the social and professional identities of the clients.